Alamat ng puno ng nara The legend of the narra tree - Matias, Segundo D. (Lampara books, 2012)
"In the old days, there was a barve and heroic leader of warriors named Nar. The datu believed Nar was given to them by Bathala. He was born a warrior so he could protect the Philippine islands from being conquered by foreign invaders. But time when Nar dreamed of leading a peaceful life with his wife, except that the call for heroism for the sake of the motherland proved stronger. In his burial ground there grew a mighty, sturdy, and strong tree."--